Effect of type of prepue on seman production performance of Frieswal bulls - MANDAL, D K; TYAGI, S; KUMAR, M (The Indian Journal of Animal Sciences, 2011)
Frieswal bulls (47) were classified as type 1 (prepucial sheath very closely attached to abdomen), type 2 (loosely attached) and type 3 (pendulous) according to prepucial morphology. Types of prepucial sheaths significantly affected the selnen volume (InI), mass activity (0-5 scale), sperm concentration (million/ml) and progressive motility (%). Spenn concentration, Inass activity and initiallnotility were highest in type 1 bulls. Bulls with pendulous sheath had lowest spenn concentration, Inass activity and initial motility, but highest selnen volunle. Rejection rates of ejaculates subjected to cryopreservation were higher in bulls having pendulous prepucial sheaths. In type 3 only 15.46% ejaculates were frozen with desired post-thaw Inotility (~40%), whereas, in type 2 and type 1 bulls it was 22.68 and 28.11 %, respectively. It was concluded that bulls with pendulous prepucial sheaths produced pOOf quality semen with lower spern1 concentration, nlass activity, initial motility per cent and poorer freezability as compared to bulls with tightly and/or moderately attached prepucial sheaths.Â